Pandemic online learning: a 'digital divide' for disadvantaged pupils?. Issue 3 (2nd March 2021) - Oldershaw, Richard; Anderson, Angela
Abstract : Richard Oldershaw, lead adviser, and Angela Anderson, legal adviser, at the Child Law Advice Service, set out the basis for the judicial review over measures put in place to support pupils to learn remotely